(untitled) (Journal of Educational Sciences, 2016)
The article reveals the struggle of Azerbaijani teachers for teaching in mother tongue in the early XX century. Substantiated by the fact, that mother-tongue education, the creation of new national schools and textbooks in their native language, training and socialization of education, the introduction of new teaching methods, the defi nition of education and educational purposes determine the motive of their action.